Analysis Of The Possibility Of Increasing The Efficiency Of The Ozone Electrosynthesis Process - Muzafarov Sh. M; Kilichov O. G; Ruzikulov Z. Z (Zien Journals, 2025)
The article provides information about the existing methods of ozone electrosynthesis and identifies their drawbacks. Based on the analysis of processes in the power supply circuit of ozone generators with sinusoidal and pulse voltage of high duty cycle, the possibility of reducing losses and increasing efficiency, increasing the yield of ozone, is substantiated. The distribution of the electric field intensity over the elements of a cylindrical ozone generator was analyzed when it was powered by a sinusoidal and periodic pulse voltage with a duty cycle of more than 5. It was found that it is possible to generate ozone without pre-cooling and drying the air, or cooling the dielectric barrier with running water
Keywords: Ozone; electrosynthesis; sinusoidal; pulse voltages